Perturbative momentum transport in MAST L-mode plasmas. (28th March 2017) - Guttenfelder, W.; Field, A.R.; Lupelli, I.; Tala, T.; Kaye, S.M.; Ren, Y.; Solomon, W.M.
Abstract: Non-axisymmetric magnetic fields are used to perturbatively probe momentum transport physics in MAST L-mode plasmas. The low beta L-mode target was chosen to complement previous experiments conducted in high beta NSTX H-mode plasmas ( β N   =  3.5–4.6) where an inward momentum pinch was measured. In those cases quasi-linear gyrokinetic simulations of unstable ballooning micro-instabilities predict weak or outward momentum convection, in contrast to the measurements. The weak pinch was predicted to be due to both electromagnetic effects at high beta and low aspect ratio minimizing the symmetry-breaking of the instabilities responsible for momentum transport. In an attempt to lessen these electromagnetic effects at low aspect ratio, perturbative experiments were run in MAST L-mode discharges at lower beta ( β N   =  2). The perturbative transport analysis used the time-dependent response following the termination of applied 3D fields that briefly brake the plasma rotation (similar to the NSTX H-mode experiments). Assuming time-invariant diffusive ( χ φ ) and convective ( V φ ) transport coefficients, an inward pinch is inferred with magnitudes, ( RV φ / χ φ )  =  (−1)–(−9), similar to those found in NSTX H-modes and in conventional tokamaks. However, if experimental uncertainties due to non-stationary conditions during and after the applied 3D field are considered, a weak pinch or even outward convection is inferred, ( RV φ / χ φ )  =  (−1)–(+5). Linear gyrokinetic simulations indicate that for these lower beta L-modes, the predicted momentum pinch is predicted to be relatively small, ( RV φ / χ φ )sim   ≈  −1. While this falls within the experimentally inferred range, the uncertainties are practically too large to quantitatively validate the predictions. Challenges and implications for this particular experimental technique are discussed, as well as additional possible physical mechanisms that may be important in understanding momentum transport in these low aspect ratio plasmas.